2021
DOI: 10.1063/5.0059461
|View full text |Cite
|
Sign up to set email alerts
|

Noise-driven topological changes in chaotic dynamics

Abstract: Noise modifies the behavior of chaotic systems in both quantitative and qualitative ways. To study these modifications, the present work compares the topological structure of the deterministic Lorenz (1963) attractor with its stochastically perturbed version. The deterministic attractor is well known to be “strange” but it is frozen in time. When driven by multiplicative noise, the Lorenz model’s random attractor (LORA) evolves in time. Algebraic topology sheds light on the most striking effects involved in su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…The deterministic concept of branched manifold (Williams, 1974) was extended to the stochastic framework by redefining it locally as an integer-dimensional set in phase space that robustly supports the point cloud associated with the system's invariant measure at each time instant. The numerical results show that BraMAH captures LORA's timeevolving homologies (Charó et al, 2021b), as shown here in Fig. 18.…”
Section: Algebraic Topology and Noise-driven Chaosmentioning
confidence: 59%
See 4 more Smart Citations
“…The deterministic concept of branched manifold (Williams, 1974) was extended to the stochastic framework by redefining it locally as an integer-dimensional set in phase space that robustly supports the point cloud associated with the system's invariant measure at each time instant. The numerical results show that BraMAH captures LORA's timeevolving homologies (Charó et al, 2021b), as shown here in Fig. 18.…”
Section: Algebraic Topology and Noise-driven Chaosmentioning
confidence: 59%
“…In Sec. 3.1, we present the rather novel approach of Branched Manifold Analysis through Homologies (BraMAH) (Sciamarella and Mindlin, 2001;Charó et al, 2021b) for approximating the branched manifolds (Birman and Williams, 1983a, b) of dynamical systems by a cell complex that allows one to characterize the manifold by its homology group in phase space (Poincaré, 1895;Sciamarella and Mindlin, 1999). The detection and description of localized coherent sets (LCSs) in twodimensional flows in physical space by BraMAH-based methods is reviewed in Sec.…”
Section: Algebraic Topology and Chaotic Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations